Computing a Counting Polynomial of an Infinite Family of Linear Polycene Parallelogram Benzenoid Graph P(a,b) - Farahani, Mohammad Reza (JOURNAL OF ADVANCES IN PHYSICS, 2013)
Omega polynomial was defined by M.V. Diudea in 2006 as Â where the number of edges co-distant with e is denoted by n(e). One can obtain Theta Î˜, Sadhana Sd and Pi Î  polynomials by replacing xn(e) with n(e)xn(e), x|E|-n(e) and n(e)x|E|-n(e) in Omega polynomial, respectively. Then Theta Î˜, Sadhana Sd and Pi Î  indices will be the first derivative of Î˜(x), Sd(x) and Î (x) evaluated at x=1. In this paper, Pi Î (G,x) polynomial and Pi Î (G) index of an infinite family of linear polycene parallelogram benzenoid graph P(a,b) are computed for the first time.